Effect of inner pipe type on the heat transfer performance of deep-buried coaxial double-pipe heat exchangers. (January 2020) - Li, Chao; Guan, Yanling; Yang, Ruitao; Lu, Xiong; Xiong, Wenxue; Long, Anjie
Abstract: In the present study, based on the currently used deep-buried coaxial double-pipe heat exchange systems for closed loop heat extraction, the influence of several inner pipe types on the heat transfer performance of buried pipe systems is analyzed. The deep-buried coaxial double-pipe with a smooth inner pipe used in current practice was taken as an example, and a full-scale three-dimensional (3D) numerical model coupling the heat transfer processes inside and outside the pipe was established by using a depth of 50 m and taking into account the modeling workload. Based on this model, full-scale 3D numerical models of coaxial double-pipes with spiral and corrugated pipes as the inner pipe types were established, and numerical analysis of heat transfer was performed. The results indicated that the heat transfer capacity of the buried pipe system can be improved by changing the shape of the inner pipe. However, the influence of the inner pipe type on heat transfer was far lower than that of the water flow rate circulating inside the buried pipe system and the initial ground temperature. Highlights: 3D numerical models of coaxial double-pipes at a depth of 50 m were established. The models included smooth, spiral, and corrugated inner pipe types. The effect of inner pipe types on heat transfer enhancement was calculated and compared. The effect of ground temperature, flow rate, and pipe type on heat transfer was compared.